Peningkatan Prestasi Belajar Siswa Kelas VII Menggunakan Metode Belajar Kelompok (Learning Group) di MTs. Al Kautsar Ranggo - Fitriani (Jurnal LENTERA: Jurnal Studi Pendidikan, 2021)
This research aims to determine 1). the influence of student achievement by using a learning group on the subjects of civic education for class VII MTs. Al Kautsar Ranggo Village, Pajo District, Dompu Regency, to achieve the research objectives, this research uses observation data collection techniques, documentation, and interviewing respondents, while the research procedures are planning, implementing, and observing. Based on the research results obtained 1). Problems faced by civic education teachers in improving MTs student achievement. Al Kautsar, Ranggo Village, Pajo District, Dompu Regency, is that the attitude of students when teaching and learning are still low because it is caused by the students themselves, and the lack of supporting facilities and infrastructure for the smooth teaching and learning process. 2). Learning achievement in civics class VII MTs. Al Kautsar, Ranggo Village, Pajo Subdistrict, Dompu Regency, on average increased, this was evidenced by the grade VII report card scores from 6.5 to 8.0. 3). The solutions were taken by civic education teachers in overcoming the problems faced by citizenship education teachers to improve student achievement in MTs. Al Kautsar, Ranggo Village, Pajo District, Dompu Regency, by guiding its students